The characteristics and relevant factors of Pap smear test use for women with intellectual disabilities in Taiwan - Yen, Suh-May (BioMed Central, 2014)
BACKGROUND: This study examines the Pap smear usage conditions and relevant influential factors for 18,204 women aged 30 years and above with intellectual disabilities, using nationwide data from 2008. METHODS: The research method of this study is secondary data analysis. The data was obtained from three nationwide databases from 2006 to 2008. This study employed descriptive statistics to analyze the use and rate of Pap smear testing by women with intellectual disabilities. Chi-square test was used to assess the correlation between Pap smear test usage and several variables. Logistic regression analysis was employed to explore the factors that influence Pap smear test usage. RESULTS: The results show that 4.83% (n =880) of women with intellectual disabilities underwent Pap smear tests. Pap smear test usage rates exhibit a declining trend with increases in age. Factors that significantly influence Pap smear test use include age, urbanization level of resident area, monthly salary, aboriginal status, marital status, existence of DM, severity of disability. CONCLUSIONS: The women with intellectual disabilities had a low use rate of Pap smear test, which is significantly less than the 28.8% usage rate for the general population of women aged 30 years and above.